Aesthetics and the Problem of Evil. - Nussbaum, Charles (Metaphilosophy, 2003)
Much of Western speculative metaphysics has subscribed to what has been called “explanatory rationalism,” which holds that there is a reason for everything that is and for the way everything is. Theodicies, or metaphysical attempts to solve the problem of evil, have relied on a special application of this principle of explanatory rationalism, namely, the principle of plenitude, which holds that the evil in the world is a necessary ingredient in the world's overall perfection or degree of reality. This essay argues that the principle of plenitude is aesthetically motivated, and that only in art and perhaps in revealed religion can the demands of explanatory rationalism be satisfied.